Systematic Literature Review: Kemampuan Pemahaman Konsep Matematis Ditinjau Dari Adversity Quotient - Vivied Eka Pratiwi; Wardani Rahayu (Griya Journal of Mathematics Education and Application, 2025)
Adversity Quotient (AQ) has an effect on improving the ability to understand mathematical concepts. In addition, with the AQ possessed by students, their mathematical concept understanding will be good. This study aims to review the literature related to the ability to understand concepts reviewed from AQ. The research method used is Systematic Literature Review. Data collection was carried out by reviewing articles that have research topics on the ability to understand concepts and AQ. Data collection comes from journals indexed by Sinta, ERIC and Google Scholar for the last 5 years. The articles obtained were 50 articles from national and international journals. From the search, a filtering process was carried out so that 20 articles were obtained that met the criteria. Then, the data collection was analyzed as research findings using qualitative and quantitative analysis. Based on the results and discussion, it was found that students who have high AQ tend to be more effective in facing challenges in learning mathematics and are able to overcome difficulties, especially by understanding the concepts to be able to solve mathematical problems.